2005
DOI: 10.1159/000089381
|View full text |Cite
|
Sign up to set email alerts
|

Caries Prevalence and Treatment Needs of 12-Year-Old Children in the Islamic Republic of Iran

Abstract: Objective: To assess the prevalence of dental caries and treatment needs of 12-year-old children living in Teheran and a rural area surrounding Esfahan. Subjects and Methods: A total of 1,102 pupils were examined clinically for caries according to WHO criteria. One calibrated dentist examined all children. Results: Of the children studied, 63.8% had sound permanent dentition, 9.9% had filled teeth and 26.3% needed treatment. The mean DMFT value found was 0.77 (DFS: 1.19). The D component was 58.7%, the M compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 35 publications
3
22
5
Order By: Relevance
“…We documented a higher mean DMFT compared to what was reported in a 2006 Iranian study on 12-year-olds [16]. Part of this discrepancy could be ascribed to the different age groups studied, and the children in the 2006 study resided in Tehran and Isfahan, not Tehran only.…”
Section: Discussioncontrasting
confidence: 57%
“…We documented a higher mean DMFT compared to what was reported in a 2006 Iranian study on 12-year-olds [16]. Part of this discrepancy could be ascribed to the different age groups studied, and the children in the 2006 study resided in Tehran and Isfahan, not Tehran only.…”
Section: Discussioncontrasting
confidence: 57%
“…The previous national and international studies reported that people with lower SR had poorer oral health than people with higher SR [5,6,7,8,9,20,21,22,36]. The results of our study imply that the lower availability of dentists for these people may partly explain the disparity in oral health.…”
Section: Discussionsupporting
confidence: 45%
“…However, the lack of data on these disorders confined us to control for them. It should be noted that the previous studies in Iran [20,21,22] have shown that people with lower SR have higher need of dental services. This implies that the disparity of dentists may be more profound than what was found in our study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another study in 12-year-old students from two cities of Yazd and Hadi-Shahr (Central Iran) [20], reported that DMFT score was reported to be 1.8±1.75, and 74.73% of the students were found to have caries. Study of Momeni et al;[[21] [23] in a study involving 43772 students of the fifth grade from all provinces of Iran and districts of the country, classified by gender and place of residence, found that the mean DMFT index in 12-year-old students was 1.67 in 1994. The highest prevalence of caries was seen in the first permanent molars.…”
Section: Resultsmentioning
confidence: 99%